Bentuk Penyajian Lagu Daerah Duson Kelahiran pada Tim Seni Kota Prabumulih - Hammam, Fakhry; Putra, Rio Eka; Sepdwiko, Deria (Indonesian Research Journal on Education, 2023)
The purpose of this study was to determine the form of presentation of the Duson Birth RegionalSong at the Prabumulih City Art Team. This type of research uses descriptive qualitative researchmethods, namely by presenting data and using a sentence in the form of text. The object of thisresearch is the songwriter teacher Duson Kelahira, while the informant is a member of the Prabumulih City Art Studio. Qualitative research method is a research process that begins withthe rules of thinking and formulating basic assumptions that will be included in the research. The results of the study found that the community in Prabumuih City lacked interest in the existingTraditions and Culture so that the birth of the Duson Song was created to give a message tooutsiders that Prabumulih City is rich in Natural Resources (SDA) such as Oil, Gas, Rubber, Palm, Pineapple, and Cultural Traditions that are still very beautiful in the Prabumulih City community.